Fun Selfies: a series of images about the artists’ images. - Rizolli, Marcos (Revista ARA, 2021)
The Fun Selfies digital photography series presents itself as artistic acts interested in thinking about the universe of artistic images through the appropriation of images by the artists themselves, initially disregarding the works they produced and that highlighted them in the History of Art. To, later, rescue their artisticities in open dialogues with their productions – visualities, processes, creative methods.